Nanosized Being of Ionic Surfactant Micelles: An Advanced View on Micellization Process - Olga S. Zueva; Mariia A. Kazantseva; Yuriy F. Zuev (Colloids and Interfaces)
An advanced model of ionic surfactant micellization has been developed. The structural and kinetic properties of micelles were analyzed in parallel from a universally accepted point of view and taking into account the principles of quantum mechanics, the phenomenon of ion pairing in the Stern layer, the symmetry considerations, and the chaos theory. It was shown that a micelle can be considered as a layered fullerene-like structure with a cavity in its center, possessing the solid-like properties of micelles in radial directions and the liquid-like properties in the perpendicular ones, allowing for water penetration between the surfactant head group and nearby methylene groups. The dimensions of the minimal fullerene-like structure formed by the terminal hydrogen atoms of surfactant methyl groups around the central cavity, unable to be occupied by surfactant tail fragments, were estimated. It was indicated that permanently occurring surfactant self-organization/disintegration needs a probabilistic description and revision of processes occurring in micellar systems built by ionic surfactants. It was noted that the probabilistic approach alters the mechanism of colloidal dissolution of hydrocarbon compounds and their solubilization by micelles. The advanced model proposes the same macroscopic properties of micelles as the classical one but modifies the structural characteristics of micelles on the nanoscale.